Large eddy simulations of compressor turbulence - Nawab, A (2020)
The DPhil thesis enclosed herein reports an investigation into turbulence in compressor passages, carried out using large eddy simulations (LES) of a repeating compressor stage. The thesis starts with a description of all the numerical tools used to conduct the research. First, the underlying assumptions of LES, as well as the governing equations and the discretization methods used in the in-house CFD solver, AU3X, are explained. This is followed by a brief account of the mesh generator developed in the current DPhil. Its ability to generate high-quality multi-block structured grids of turbomachinery blade passages, whilst also ensuring perfectly-balanced domain partitioning, is demonstrated. Finally, a novel sliding plane algorithm, developed with the aim of minimizing the communication cost in massively-parallel computations, is presented.